2022
DOI: 10.1021/acssensors.2c00352
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Investigation on α-MoO3 (100): Amines Adsorption and Surface Chemistry

Abstract: The (100) surface of α-MoO3 should possess overwhelmingly more exposed Mo atoms than the (010), and the exposed Mo has been extensively considered as an active site for amine adsorption. However, α-MoO3 (100) has drawn little attention concerning the amine sensing mechanism. In this research, adsorption of ammonia (NH3), monomethylamine (MMA), dimethylamine (DMA), and trimethylamine (TMA) is systematically investigated by density functional theory (DFT). All four of these molecules have high affinity to α-Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The adsorption energy window was set at 100 kcal/mol and minimum energy difference set at 0.0 kcal/mol. In the DFT study, the adsorption energy ( E ad , eV) is defined in eq : ,, E ad = ( E surface + adsorbate ) ( E surface + E adsorbate ) where E surface+adsorbate represents the total energy of the interacting catalyst’s surface and the adsorbate, while E surface + E adsorbate is the energies of the catalyst’s surface and the free adsorbate in the gas phase. This equation reveals that the more negative E ad , the stronger the adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption energy window was set at 100 kcal/mol and minimum energy difference set at 0.0 kcal/mol. In the DFT study, the adsorption energy ( E ad , eV) is defined in eq : ,, E ad = ( E surface + adsorbate ) ( E surface + E adsorbate ) where E surface+adsorbate represents the total energy of the interacting catalyst’s surface and the adsorbate, while E surface + E adsorbate is the energies of the catalyst’s surface and the free adsorbate in the gas phase. This equation reveals that the more negative E ad , the stronger the adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption energy window was set at 100 kcal/mol and minimum energy difference set at 0.0 kcal/mol. In the DFT study, the adsorption energy (E ad , eV) is defined in eq 9: 12,37,38 The weaker adsorption of CH 3 CO* on the Pd/OLC and Pd-CeO 2 /OLC predicts better electrocatalytic conversion of the acetyl to acetic acid on the OLC-based electrodes. The E ad of Pd-CeO 2 /OLC is 1.87% higher than that of the Pd/OLC, but this seems to be compensated by the excellent conductivity of the Pd-CeO 2 /OLC (i.e., reduced band gap of 0.176 versus 0.433 eV).…”
Section: Performance In Electrocatalytic Detection Of Ethanolmentioning
confidence: 99%
“…In the DFT calculation, the adsorption energy, E ad (eV), is defined as ( eq 9 ) 43 , 62 , 63 where E surface + adsorbate is the total energy of the interacting catalyst surface and the adsorbate and E surface + E adsorbate is the energies of the bare catalyst surface and the free adsorbate in the gas phase. This equation shows that the more negative the E ad value, the stronger the adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced sensing properties primarily arise from the adsorption of W atoms with O atoms in acetone, yet the crucial component of C in VOCs has been overlooked. Kang et al prepared C-doped Co 3 O 4 , and the density functional theory (DFT) calculations showed that the doping sites displayed a unique electronic structure, significantly enhancing the glucose sensor performance. Gao et al found that the cobalt sites in P–Co 3 O 4 have better affinity, easier electron transfer, and stronger bond-weakening capacity for peroxymonosulfate than those in nondoped Co 3 O 4 , resulting in increased catalytic activity.…”
Section: Introductionmentioning
confidence: 99%